Driver behavior with a smartphone collision warning application – A field study. (January 2017) - Botzer, Assaf; Musicant, Oren; Perry, Amir
Highlights: Drivers decelerated when a collision warning smartphone application issued warnings. Drivers decelerated more strongly when they used the application more times. Drivers received fewer warnings the more times they used the application. Abstract: The potential of collision warning systems (CWS) to prevent or mitigate rear end collisions has been repeatedly demonstrated in both simulator and on-road studies. Still, their market penetration rate has remained slow. Collision warning smartphone applications (CWSA) may assist in stimulating wider adoption of collision warning technology, as they are considerably less expensive and are immediately accessible through smartphone app stores. However, driver behaviors with such applications have never been studied. Twenty-six drivers participated in this study and used CWSA during their daily on-road trips for a period of one to two weeks. Their time-stamped acceleration and warnings were recorded and analyzed. We found that CWSA generated safer driving behaviors as decelerating in response to warnings of imminent collisions and receiving fewer collision warnings overtime. Nevertheless, twenty-one drivers reported that they stopped using the application after the experiment ended. In view of the high market penetration rate of smartphones, together with the potential of CWSA to generate safer driving behaviors, we recommend developing incentive programs to encourage usage.